The Netflix Of Learning: Using Youtube Contents In Teaching Ilqa’ Abqari Public Speaking Model - Zulkarnin Zakaria; Myra Aidrin Mohd Ali; Tg Ainul Farha Tg Abdul Rahman; Abdel Rahman Ibrahim Suleiman Islieh; Nur Aisyah Mohamed; Nur Amirash Che Soh (Journal of Management Information and Decision Sci, 2024)
Indexed by ERA